2005
DOI: 10.1111/j.1572-0241.2005.40093.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Pneumatic Dilation in the Treatment of Achalasia

Abstract: Although 51.4% of patients continued to be in clinical remission more than 15 yr after the initial pneumatic dilation, the long-term success rate of pneumatic dilation seems to drop progressively with time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
85
6
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(101 citation statements)
references
References 23 publications
9
85
6
1
Order By: Relevance
“…PD is easier to perform, and has the advantages of a shorter hospitalization and lower cost compared with surgery and had a better long-term efficacy than endoscopic botulinum toxin injection (9,11,12). The major concern of PD is that its long-term efficacy may not be that satisfactory (13,14). However, researchers have noticed an interesting fact: the recurrence rate after PD for achalasia inversely correlated with patient age, an older age is a favorable predictive factor for a good long-term efficacy (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PD is easier to perform, and has the advantages of a shorter hospitalization and lower cost compared with surgery and had a better long-term efficacy than endoscopic botulinum toxin injection (9,11,12). The major concern of PD is that its long-term efficacy may not be that satisfactory (13,14). However, researchers have noticed an interesting fact: the recurrence rate after PD for achalasia inversely correlated with patient age, an older age is a favorable predictive factor for a good long-term efficacy (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence is a major concern after endoscopic and/or surgical treatment of achalasia, and several factors have been found to be associated with treatment failure, type III in HRM, young patients (< 40 years old), males had an unfavorable outcome in PD (2,11,13,25), and incomplete myotomy, an excessively tight anti-reflux wrap andsigmoid-type achalasia were associated with treatment failure in HM (26). In the present study, three cases had a recurrence, and multiple analysis revealed that sigmoid-type achalasia was a risk factor of treatment failure.…”
Section: Discussionmentioning
confidence: 99%
“…A reduction of dysphagia in patients subjected to the above-mentioned procedure concerns 58-95% (15)(16)(17)(18)(19). The relatively low percentage of postoperative complications: mortality<1%, esophageal perforation 2-4%, reflux symptoms-5%, and low treatment costes speaks in favor of the procedure (14,(19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…Pneumatic balloons are convenient for dilating the spastic cardiac sphincters forcefully and mechanically, leading to the partial rupture of smooth muscle fibers, but with definitive outcomes. Karamanolis et al [24] reported successfully treating 75.8% of their achalasia patients with one-course dilation, whereas only 1 patient developed a procedure-related complication (esophageal perforation). Additionally, the curative effects were still present in 51.4% of the dilated patients at the postoperative year 15 follow-up visits.…”
Section: Discussionmentioning
confidence: 99%